1993
DOI: 10.2307/1602543
|View full text |Cite
|
Sign up to set email alerts
|

Review of Research on Home Visiting for Pregnant Women and Parents of Young Children

Abstract: In this paper, David Olds and Harriet Kitzman review the results of the experimental literature concerning the effectiveness of home visiting programs in improving the lives of children and families. Their extensive review concentrates on randomized trials, that is, those most methodologically rigorous studies of all in which families are randomly assigned to two groups, typically to receive either (1) home visiting services (the experimental group) or (2) care as usual (the control group). Olds and Kitzman fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
241
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(252 citation statements)
references
References 52 publications
7
241
0
4
Order By: Relevance
“…Previous reviews suggesting that home visiting for preterm infants may improve outcomes were published ∼20 years ago. 10,11 Since that time, the preterm birth rate in the United States has risen by 20%. Recent literature on the epidemiology of preterm birth has also revealed the public health impact of late preterm birth, or delivery between 34 and 36 weeks' gestation, which affects 70% of all infants born preterm.…”
mentioning
confidence: 99%
“…Previous reviews suggesting that home visiting for preterm infants may improve outcomes were published ∼20 years ago. 10,11 Since that time, the preterm birth rate in the United States has risen by 20%. Recent literature on the epidemiology of preterm birth has also revealed the public health impact of late preterm birth, or delivery between 34 and 36 weeks' gestation, which affects 70% of all infants born preterm.…”
mentioning
confidence: 99%
“…31 Services may be particularly effective for some subgroups of participants but have little impact with others. [37][38][39][40][41] First-time adolescent mothers appear to be especially amenable to intervention through home visitation. 39,42 On the other hand, maternal depression, common among young mothers and a risk factor for maltreatment, may impede the ability of programs to reduce child abuse and neglect.…”
Section: Discussionmentioning
confidence: 99%
“…The growth in early intervention has occurred because research findings of program evaluations have continued to report positive developmental gains for the child and improved family functioning. Moreover, long-term studies (Barnett, 1993(Barnett, , 1997Olds & Kitzman, 1993) of early intervention programs have shown that these highly specialized and comprehensive services are cost effective because they reduce demands on health, education, and justice. Typically, such services are designed to provide primary or secondary intervention to the child and family.…”
Section: Overviewmentioning
confidence: 99%
“…In a review of the experimental literature regarding the effectiveness of home-visiting programs that incorporated randomized trials, aIds and Kitzman (1993) examined 31…”
Section: Home Visiting Programsmentioning
confidence: 99%
See 1 more Smart Citation